Silenciamiento transcripcional en el trivalente sexual meiótico de murciélagos pertenecientes al género Artibeus, familia Phyllostomidae - Barajas Ruiz, Angie (2014)
The sex-chromosome system among many bat species of the Artibeus genus, which belong to the family Phyllostomidae, is an exception to the general pattern of sex determination XX / XY among eutherian mammals: they have a multiple sex chromosome system which forms an XY1Y2 body with two synaptic regions between X- Y1 and X- Y2.\nCombining electron microscopy and fluorescent immunolocalization techniques of specific meiotic protein, the results of this thesis show the presence of histone variant ?-H2AX and BRCA1 in the asynaptic segments of the differential regions of the XY1Y2 body, suggesting that these regions are transcriptionally silenced. Moreover, it is confirmed the diploid number, the chromosome morphology, the ultrastructure sequential, and the trivalent XY1Y2 sex determination in A. lituratus and A. planirostris. Furthermore, it is suggested that basic mechanism of meiosis that prevents the spreading of chromatin inactivation to the autosomal segments of the XY1Y2 body in both species, is not the presence of NORs.\nThe present work allows advancing in the comprehension of the basic mechanisms of meiosis in mammals, including human carriers of structural chromosomal rearrangements.